2014
DOI: 10.1093/toxsci/kfu260
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated Short Single-Walled Carbon Nanotubes But Not Plain and Multi-Walled Short Carbon Nanotubes Show in vitro Genotoxicity

Abstract: Long carbon nanotubes (CNTs) resemble asbestos fibers due to their high length to diameter ratio and they thus have genotoxic effects. Another parameter that might explain their genotoxic effects is contamination with heavy metal ions. On the other hand, short (1-2 µm) CNTs do not resemble asbestos fibers, and, once purified from contaminations, they might be suitable for medical applications. To identify the role of fiber thickness and surface properties on genotoxicity, well-characterized short pristine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
(77 reference statements)
1
22
0
Order By: Relevance
“…Exposure to SWCNTs has been associated with increased levels of double strand breaks (measured by γH2AX immunostaining) in human lymphocytes (Cveticanin et al 2010) and A549 cells (Mrakovcic et al 2015). Another study showed unaltered levels of γH2AX immunostaining in human mesothelial cells, although the levels were regarded to be nominally increased (approximately 1.2-fold) (Pacurari et al.…”
Section: Genotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to SWCNTs has been associated with increased levels of double strand breaks (measured by γH2AX immunostaining) in human lymphocytes (Cveticanin et al 2010) and A549 cells (Mrakovcic et al 2015). Another study showed unaltered levels of γH2AX immunostaining in human mesothelial cells, although the levels were regarded to be nominally increased (approximately 1.2-fold) (Pacurari et al.…”
Section: Genotoxicitymentioning
confidence: 99%
“…In addition, 13 out of 18 studies report increased micronuclei frequency in human cell lines after exposure to MWCNTs, including three independent studies of MWCNT-7 (Muller et al 2008a, 2008b; Asakura et al 2010; Cveticanin et al 2010; Migliore et al 2010; Di Giorgio et al 2011; Srivastava et al 2011; Kato et al 2013; Wu et al 2013; Darne et al 2014; Tavares et al 2014; Visalli et al 2015; Kim et al 2016); five studies showed null effects (Szendi & Varga 2008; Thurnherr et al 2011; Lindberg et al 2013; Ponti et al 2013; Mrakovcic et al 2015). Eight out of 13 studies report increased micronuclei frequency in human cell lines after exposure to either SWCNTs or MWCNTs (Cveticanin et al 2010; Migliore et al 2010; Cicchetti et al 2011; Di Giorgio et al 2011; Kisin et al 2011; Manshian et al 2013; Darne et al 2014; Kim & Yu 2014; Kim et al 2016); five studies showed null effects (Kisin et al 2007; Lindberg et al 2009; Lindberg et al 2013; Pelka et al 2013; Mrakovcic et al 2015). Null effect studies used CNTs similar to the CNTs that caused micronuclei formation with respect to diameter, length, specific surface area and purity, although it should be emphasized that many publications contain insufficient information on fiber characteristics.…”
Section: Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro administered fSWCNTs and fMWCNTs with strong negative charge also increased genotoxicity, hampered natural killer cell function, and inhibited cell division. Of note, an increasing number of recent studies show that fCNTs exhibit enhanced genotoxicity and apoptosis induction compared to parent CNTs, but the opposite for cellular damage and cytotoxicity assays, possibly due to uptake route (Alam et al, 2016; Mrakovcic et al, 2015; Ursini et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In an extensive study Mrakovcic et al [95] Among metallic nanoparticles, gold nanoparticles (AuNPs) are the most promising and most widely used systems used for therapeutic, diagnostic or 'theranostic' applications. Boisselier et al [96] (2009) provides a good overview of the preparation, the field of applications and the cytotoxicity of AuNPs.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%